2009
DOI: 10.1080/15256480902850943
|View full text |Cite
|
Sign up to set email alerts
|

Does Franchising Create Value? An Analysis of the Financial Performance of US Public Restaurant Firms

Abstract: Executive Summary:It is commonly believed that the franchising method of distribution provides strategic and operational benefits to the companies that adopt it. These benefits should result in superior financial performance as compared to that of firms that do not use franchising.Yet, the empirical evidence of the effects of franchising on financial performance is sparse and mixed. The purpose of this paper is to further examine the empirical evidence of the impact of franchising on a firm's financial perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…First, from the aspect of resource constraints, the franchisees finance the outlet, freeing the franchisor from the pressure of capital expenditure and provide managerial knowledge to fuel franchisor growth (Oxenfeldt and Kelly, 1969;Hunt, 1973;Norton, 1988;Shane, 1998). Second, economy of scale in purchasing and advertisement can be achieved more rapidly by franchising than by company-owned units (Aliouche and Schlentrich, 2005;Justis and Judd, 1998;Spinelli et al, 2003). Third, because franchisees are owner-managers of franchised units, franchising can reduce franchisor monitoring costs (Lafontaine and Kaufmann, 1994).…”
Section: Related Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, from the aspect of resource constraints, the franchisees finance the outlet, freeing the franchisor from the pressure of capital expenditure and provide managerial knowledge to fuel franchisor growth (Oxenfeldt and Kelly, 1969;Hunt, 1973;Norton, 1988;Shane, 1998). Second, economy of scale in purchasing and advertisement can be achieved more rapidly by franchising than by company-owned units (Aliouche and Schlentrich, 2005;Justis and Judd, 1998;Spinelli et al, 2003). Third, because franchisees are owner-managers of franchised units, franchising can reduce franchisor monitoring costs (Lafontaine and Kaufmann, 1994).…”
Section: Related Theoriesmentioning
confidence: 99%
“…Resource scarcity theory and agency theory are the two dominant theories to explain the motivation of firms to decide franchising (Aliouche and Schlentrich, 2005). Resource scarcity theory explains that franchising allow franchisor firms to use franchisees' capital and managerial expertise to accelerate growth to reach minimum efficient scale and build brand name capital (Hunt, 1973;Norton, 1988;Oxenfeldt and Thompson, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…A few empirical studies have compared the financial performance of franchised and non-franchised firms, and the results are inconclusive. Some found that franchisors have created more value than their non-franchisor competitors (Spinelli et al, 2003;Aliouche and Schlentrich, 2005), the other found no significant differences in financial performance between franchised and non-franchised firms (Alon et al, 2004). Because the restaurant industry is the largest franchising industry (Michael, 2002), this study examined this issue by including a dummy variable to control the potential effect of franchising on a firm's intangible assets.…”
Section: Control Variablesmentioning
confidence: 99%
“…The main reason for the lack of research in this area is due to limited availability of performance data, since a large majority of franchising firms are privately held companies. Despite this limitation, several studies have used publicly available information to research the performance effects of franchising compared to their non-franchising counterparts (Roh, 2002;Leleux et al, 2003;Hsu and Jang, 2009;Aliouche and Schlentrich, 2009). The results from these studies show mixed results; however, the most recent studies reveal strong evidence that franchising produces superior financial performance compared to non-franchising companies, particularly in the restaurant industry (Madanoglu et al, 2011;Aliouche et al, 2012).…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Although several studies have investigated the performance effects of franchise firms (Leleux et al, 2003;Aliouche and Schlentrich, 2009;Hsu and Jang, 2009;Madanoglu et al, 2011;Aliouche, Kaen and Schlentrich, 2012), no previous study has focused on the performance effects of corporate real estate ownership on franchise restaurant companies. McDonald's was one of the earliest of companies that have extensively used CRE as a source of strategic advantage and as a way to reduce the agency costs associated with franchising.…”
mentioning
confidence: 99%